Recovery of Campylobacter from External and Internal Spleen Samples from Baby Broiler Chicks Following Various Routes of Inoculation. Issue 1 (16th August 2015) - Cox, N.A.; Richardson, L.J.; Cosby, D.E.; Berrang, M.E.; Harrison, M.A.
Abstract: Campylobacter have been found in lymphoid tissue of poultry, but the location in these tissues has not been determined. The objective of this study was to determine if Campylobacter are on the outside or on the inside of the spleen. For external (ES) spleen sampling 2 days post‐inoculation, each spleen was rinsed with 3 mL of Bolton's enrichment broth (BEB). For internal (IS) spleen sampling, each rinsed spleen was submerged into 70% ethanol for 10 s, removed and submerged into 0.85% saline. The spleen was then placed into a sterile bag, macerated with 3 mL of BEB and stomached for 30 s before incubation. All samples and the correlating ceca were sampled for C ampylobacter jejuni . Overall in four different experiments with baby chicks inoculated by oral, ocular or cloacal routes, Campylobacter was recovered from 75% (82/109) of the ES, 71% (77/109) of the IS and from 100% (109/109) of the ceca. Ethanol and saline samples were all negative for Campylobacter, suggesting that ethanol immersion is adequate to kill C . jejuni on the external surface. With Campylobacter in the internal tissue of the spleen, the organism appears to be systemic. Further research will determine the colonization mechanisms required for this bacterium in these different tissues. Practical Applications: It is very difficult to sample the free flowing blood of a living chicken for bacteria without introducing contamination from the skin. This paper describes an effective method of sampling the internal portion of the spleen without introducing external contamination. By doing so, this indicates that the bacteria were systemic and will travel with the blood to all of the internal organs and tissues throughout the bird's body. Therefore when the bacteria are not isolated from certain tissues, it means that reservoirs were either not established or did not persist in that particular tissue even though the bacteria did flow through with the blood. Unless all of the potential reservoirs and sources of bacteria such as Campylobacter and Salmonella are identified and fully understood, successful intervention strategies may not be possible. It would be important to know if reservoirs of these bacteria present in internal organs and tissues can periodically seed the intestinal and/or reproductive tracts of adult breeder birds, thus providing a source of contamination to the offspring.